Perancangan Sistem Informasi Terintegrasi untuk Manajemen Penjualan dan Inventaris guna Mendukung Efektivitas Operasional pada ArtTa Photo & Printing Pekanbaru - Sahrun, Nori; Anshori, Ikhwan; Sularno, Sularno (Prodi Sistem Informasi Universitas Dharma Andalas, 2026)
This final project is entitled “Web-Based Sales and Stock Information System at Artta Photo & Printing”. Liyana Dita Shahibbah wrote this final project guided by Ikhwan Anshori, S.Kom., M.Kom. This research was prepared to overcome various problems in the sales process and inventory management that are still done manually. These problems include frequent errors in recording transactions, delays in checking stock, and inefficient report generation. The research method used is the Waterfall method, with stages namely Analysis, Design, Implementation, Unit Testing, System Integration and Testing, and Operation and Maintenance. The designed system provides features for managing product data, sales transactions, sales reports, and stock management automatically and in real-time. The results of this system development are expected to help Artta Photo & Printing in improving work efficiency, minimizing errors in recording, and providing more accurate and structured information to support decision making.